Career destinations of University of Ghana Medical School graduates of various year groups. - Lassey, A.T.; Lassey, P.D.; Boamah, M. (Ghana medical journal, 2013)
To report on the current career destination of the University of Ghana Medical School (UGMS) qualified doctors in the year groups, 1998, 2000, 2003, 2005 and 2008. Interview of doctors from each year group currently working at the Korle-Bu Teaching Hospital corroborated by phone calls to the doctors. All Ghanaian doctors from each graduating year group. 1. Current location of employment in Ghana or abroad, 2. Gender ratios of the doctors retained in Ghana. Three hundred and seventy-two (372) UGMS doctors consisting of 353 Ghanaians and 19 foreign students graduated over the five year groups. Of the 353 Ghanaians, 113 emigrated, while all but one of the 240 living in Ghana, practice medicine. The retention rate improved from 54.2% in 1998 to 86.3% in 2008. The overall retention rate however is 68.0% while the retention rates for the male and female doctors were 69.3% and 64.6% respectively. Of the 177 doctors practicing in Ghana from the first 4 year-groups (i.e. 1998, 2000, 2003 and 2005,) 139 (i.e. 31, 31, 34 and 43 from the respective year groups) have either completed postgraduate training or are in the residency training programme. Thus 78.5% of these doctors working in Ghana have opted for postgraduate training. The establishment of the GCPS and to a lesser extent the introduction of the ADHA before it appear to have slowed down the medical brain drain as more and more doctors avail themselves of the local opportunities. The GCPS therefore needs supporting effectively in order to continue to be a strong incentive for the retention of doctors in Ghana, apart from helping to staff district general hospitals with specialists.
Keywords: Career destinations; University of Ghana; Ghanaian doctors; specialist training; medical emigration